Economic Inequality and the Geography of Activity Space Segregation: Combining Mobile Device Data and Census Data - Siwei Cheng; Yongjun Zhang; Jenna Shaw (RSF: The Russell Sage Foundation Journal of the Social Sciences)
This article combines daily mobility data collected via mobile device and the American Community Survey to create comprehensive measures of activity space segregation across geographic areas in the United States. We extend conventional measures of spatial segregation to incorporate exposure in individuals’ routine activities, weighted by the flows of individuals between census block groups. Our analysis reveals three key findings. First, metropolitan areas vary significantly in the degree of activity space segregation. Second, individuals exhibit a lesser degree of income and racial segregation in their activity space than in their residential space. Third, income inequality at the metropolitan statistical area level is associated with greater isolation for both lowest and highest income groups; economic inequality exerts a more substantial influence on activity space isolation than residential segregation.